2007
DOI: 10.1016/j.trstmh.2006.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Community support is associated with better antiretroviral treatment outcomes in a resource-limited rural district in Malawi

Abstract: CitationCommunity support is associated with better antiretroviral treatment outcomes in a resource-limited rural district in Malawi. This article was originally published in a journal published by Elsevier, and the attached copy is provided by Elsevier for the author's benefit and for the benefit of the author's institution, for non-commercial research and educational use including without limitation use in instruction at your institution, sending it to specific colleagues that you know, and providing a copy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 5 publications
0
141
1
Order By: Relevance
“…8 Communities can also contribute in a comprehensive manner to ART delivery as seen in Malawi (Table 3). 23,24 Community workers also have a positive influence on health-seeking behaviour among people with HIV/AIDS, help to reduce stigma and discrimination 24,25 and often play a critical role in adherence support. 26 People with HIV/AIDS have also been effectively mobilized as partners in the provision of care.…”
Section: Engages the Community To Address Health Needsmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Communities can also contribute in a comprehensive manner to ART delivery as seen in Malawi (Table 3). 23,24 Community workers also have a positive influence on health-seeking behaviour among people with HIV/AIDS, help to reduce stigma and discrimination 24,25 and often play a critical role in adherence support. 26 People with HIV/AIDS have also been effectively mobilized as partners in the provision of care.…”
Section: Engages the Community To Address Health Needsmentioning
confidence: 99%
“…Evidence from Lusisiki in South Africa and Thyolo in Malawi showed that the use of nurses (Type II task shifting) 19 and community cadres (Type IV task shifting) 24 in the delivery of ART significantly improved overall ART outcomes (Table 4). Thus, from a public health perspective, the use of task shifting for HIV/AIDS care at two relatively new levels of the health system (health centres and the community) did not compromise quality but, on the contrary, was associated with significantly better ART outcomes.…”
Section: Quality Of Care and Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…A possible way forward might be to offer group counselling sessions for WHO stages 1 and 2 patients in the community and at the GOPD through task-shifting to existing people living with HIV/AIDS (PLWA) groups, community volunteers and expert patients. [11][12][13][14] If these services were to be offered, there is a higher probability that continued followup visits would take place.…”
Section: Article In Pressmentioning
confidence: 99%